2021
DOI: 10.3390/ph14111064
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Peptide-Gadolinium Nanocomplexes as siRNA Delivery Tools

Abstract: We have recently reported that a cyclic peptide containing five tryptophan, five arginine, and one cysteine amino acids [(WR)5C], was able to produce peptide-capped gadolinium nanoparticles, [(WR)5C]-GdNPs, in the range of 240 to 260 nm upon mixing with an aqueous solution of GdCl3. Herein, we report [(WR)5C]-GdNPs as an efficient siRNA delivery system. The peptide-based gadolinium nanoparticles (50 µM) did not exhibit significant cytotoxicity (~93% cell viability at 50 µM) in human leukemia T lymphoblast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our previous studies showed that cyclic CPPs, [WR] 4 and [WR] 5 , with alternation of tryptophan (W) and arginine (R) residues, increased the cellular uptake of different compounds such as phosphopeptides, doxorubicin, ,,, paclitaxel, camptothecin, curcumin, , anti-HIV drugs, , gadolinium nanoparticles, selenium nanoparticles, gold nanoparticles, , and oligonucleotides. , Cyclic CPPs containing alternate W and R residues demonstrated improved cellular uptake delivery when compared to linear CPPs . Moreover, the uptake of both [WR] 4 and [WR] 5 was not dependent on the endocytosis pathway. , …”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that cyclic CPPs, [WR] 4 and [WR] 5 , with alternation of tryptophan (W) and arginine (R) residues, increased the cellular uptake of different compounds such as phosphopeptides, doxorubicin, ,,, paclitaxel, camptothecin, curcumin, , anti-HIV drugs, , gadolinium nanoparticles, selenium nanoparticles, gold nanoparticles, , and oligonucleotides. , Cyclic CPPs containing alternate W and R residues demonstrated improved cellular uptake delivery when compared to linear CPPs . Moreover, the uptake of both [WR] 4 and [WR] 5 was not dependent on the endocytosis pathway. , …”
Section: Introductionmentioning
confidence: 99%